Melanotic neuroectodermal tumor of infancy - Hao Tran Kiem; Kim Hoa Nguyen Thi; Phu Tran Xuan; Loi Nguyen Hong; Son Nguyen Huu; Duy Phan Canh; Carlos Rodriguez Galindo; McKay McKinnon (Journal of Pediatric Surgery Case Reports, 2019)
Introduction: Melanotic neuroectodermal tumor of infancy (MNTI) is a rare, rapidly growing pigmented neoplasm of neural crest origin generally arising in infants during the first year of life. Case: We report a 15-month old male who presented with a 2-month history of a rapidly growing mass in the anterior. A biopsy showed melanotic neuroectodermal tumor, and complete resection with negative margins was subsequently achieved. The patient is in remission at 11 months from surgery. Conclusion: Due to its rapid growth potential and locally destructive behaviour, early diagnosis is extremely important to limit local expansion. The treatment of choice for melanotic neuroectodermal tumor of infancy (MNTI) is surgical excision. Keywords: Melanotic neuroectodermal tumor, Infancy